A case study on the open source software deployment for total hospital information systems at hospital Universiti Sains Malaysia (Kubang Kerian, Kelantan) / Haslinda Mohamed - Mohamed, Haslinda (2005)
This study describes the implementation of Open Source software in a large public sector organisation, Hospital Universiti Sains Malaysia, Kubang Kerian in Kelantan, Malaysia. The findings reveal a radical shift in Open Source deployment from invisible horizontal infrastructure systems to highly visible applications. The case study describes the implementation of these systems, the difficulties encountered, and also the benefits in terms of utilising the most from existing resources and the available R&D. Cost and benefits analysis are recommended to show the cost saving because these details will be useful. Furthermore, few studies have thus farquantified the savings from the deployment of Open Source software (OSS). Also, in many cases, the extra functionality available in the OSS systems deployed allowed for a richer feature set overall. The study also identifies the primary drivers in the move to OSS, namely principle, simplicity and practicality. This is useful, since, while several studies have considered the motivation of OSS developers, the motivation of the users of OSS needs attention as well. The study also indicates how a typical company can contribute back to the OSS community in their own unique way, by distributing applications from their own domain of expertise.